Dinâmica dos processos erosivos em taludes do baixo curso do Rio São Francisco : desafios para seu controle com uso de geotêxteis - Fontes, Cátia dos Santos (2016)
The Lower São Francisco River has suffered with impacts by changes in river flow caused by public policies implemented in recent decades that prioritized the construction of Electrical Power Dams. Then is very important to search for solutions through techniques to monitor the progress of erosion, especially erosion on rivebanks. From this perspective, we need to build sustainable techniques that can mitigate the soil loss controlling erosion with soil bioengineering techniques and considering the geomorphological dynamics of that environment. The objective of this work was to evaluate the dynamics of erosion on the banks of the São Francisco River in its lower course, and how to mitigate them through the use of geotextiles made from natural fibers for hydro-recovery. Thus, the methodology followed the steps: initially was based on a literature review, then field work for the area recognition and the analysis of the landscape as well as fibers identification in order to develop erosion control techniques, followed by experimental tests and monitoring geotextile evaluated in field and laboratory and then was build a synthesis of the results achieved with the research. The methodological theoretical model used in the research was the GTP (Geosystem, Territory, Landscape) proposed by Bertrand (1971), through a systemic and integrated approach to landscape analysis and the relationship between society and nature in the geographical space. The river banks erosion was registered as a result of fluvial dynamics presented by the São Francisco River, considering the regulated flow from the implementation of Sobradinho and Xingó electrical power dams in the Lower São Francisco (BSF) and associated deforestation, river margins illegal occupation, among other impacts. As a result the research states the presence of erosion on the right bank of the the lower river causing soil loss that is associated with the fluvial dynamics of the river with regulated flow, as well as the conditions of climate and soil of studied area also influence riverbank erosion. From the field experiment it was observed that among the selected fibers to perform the tests for the production of geotextiles, those of Ouricuri and Junco were more efficient in erosion control, but for strength and durability to climatic variables the fiber from Taboa, was the most resistant. In conclusion the use of natural fibers in geotextiles and its application in the riverbanks became an alternative to compose erosion control techniques, based on the results obtained through field and laboratory tests. Finally this research provides to the scientific community a contribution on the erosion on the riverbank, providing useful information for the society as an important technique to erosion control in the riverbanks.